Hunting the Grisly and Other Sketches : An Account of the Big Game of the United States and its Chase with Horse, Hound, and Rifle - Roosevelt, Theodore, 1858-1919 (Salt Lake City, UT : Project Gutenberg, 2006)
"Hunting the Grisly and Other Sketches" by Theodore Roosevelt is a collection of hunting narratives and observations written in the late 19th century. This work explores the thrilling adventures of big game hunting in the American wilderness, particularly focusing on the American buffalo and grizzly bear, detailing the experiences that shape the rugged individualism of hunters during this era. The opening of the book begins with a rich historical context about the decline of the American buffalo population, detailing the reasons for their extinction due to hunting and habitat loss driven by expansion and industrialization. Roosevelt vividly recounts the experiences of his brother and cousin as they embark on a buffalo hunt in Texas, giving insight into the challenges faced during their journey, such as hardships of travel, encounters with both wildlife and other hunters, and the excitement of hunting the vast herds of buffalo. This introduction sets the tone for a narrative steeped in adventure, nature observation, and the Author's deep respect for the American wilderness and its dwindling game. (This is an automatically generated summary.)
The bison, or American buffalo -- The black bear -- Old Ephraim, the grisly bear -- Hunting the grisly -- The cougar -- A peccary hunt on the Nueces -- Hunting with hounds -- Wolves and wolf-hounds -- In cowboy land.
Release date is 2006-04-06
Produced by Dagny; John Bickers; David Widger
Keywords: Hunting -- United States